Selling the Spirit A Semiotic Analysis of Omotenashi in the Visual and Textual Marketing of the Japan National Tourism Organization (JNTO) - Harsiwi, Windy; Wicaksono, Ajie (International Journal of Sustainable Competitiveness on Tourism, 2025)
Omotenashi, the Japanese philosophy of selfless and wholehearted hospitality, has become a central element of Japan’s national tourism identity. However, its intangible and culturally nuanced nature makes it difficult to translate into clear and appealing messages for global audiences. This study explores how the Japan National Tourism Organization (JNTO) navigates this challenge through strategic visual and textual communication. Using a semiotic analysis, the research examines signs, symbols, and meanings embedded in JNTO’s promotional videos and official website content. The analysis identifies a consistent visual vocabulary that represents Omotenashi: respectful bowing, meticulous food presentation, orderly interior spaces, and serene natural settings. These images act as symbolic cues that communicate humility, harmony, and attentiveness—core values of Omotenashi—without requiring explicit explanation. JNTO pairs these visuals with carefully selected textual expressions such as “heartfelt,” “authentic,” and “crafted with care,” which help emotionalize the viewer’s perception and frame Omotenashi as a warm, spiritual, and culturally grounded experience. The findings indicate that JNTO deliberately simplifies and aestheticizes Omotenashi to make it more accessible to international audiences. Rather than attempting to convey the full cultural complexity of this practice, JNTO constructs a romanticized narrative that positions Omotenashi as both a distinctive and desirable tourism offering. This strategy allows the organization to effectively “sell the spirit” of Japan by transforming a deeply embedded cultural value into a consumable tourism product. The study demonstrates how intangible cultural concepts can be reinterpreted through semiotic design to strengthen national tourism branding.